Acoustic Emissions and monitoring bearing health - Mba, David (Taylor & Francis, 2003)
Acoustic emission (AE) was originally developed for non-destructive testing of static structures. however, over the years its application has been extended to health monitoring of rotating machines and bearings. It offers the advantage of earlier defect detection in comparison to vibration analysis. Current methodologies of applying AE for bearing diagnosis are reviewed. The investigation reported in this paper was centered on the application of standard acoustic emissions IAE) characteristic parameters on a radially loaded bearing. An experimental test-rig was designed to allow seeded defects on the inner and outer race. It is concluded that irrespective of the radial load, rotational speed and high levels of background noise. simple AE parameters such as e.m.s. and AE counts provided an indication of bearing defect. In addition to validating already established AE techniques, this investigation focuses on establishing an appropriate threshold level for AE counts.
Keywords: Acoustic emissions; bearing defect diagnosis; condition monitoring